O diálogo entre solista e orquestra no Concerto Métis de Roland Dyens - Daniel Cordova Christofaro (2010)
This dissertation´s goal is to analyze the Concerto Métis (for guitar and string orchestra) by Roland Dyens considering the dialogue between soloist and orchestra. It will discuss the functionality of the group regarding sound balance, taking into account the sound characteristics of the guitar. Aesthetic, technical, practical and musical aspects of the Concerto Métis were observed through a critical analysis of the score backed up by a live performance held in September 2009.